“Dentro e fora da comunidade do atalho”: uma etnografia quilombola na Mesorregião do Triangulo Mineiro e Alto-Paranaíba. - Feitosa, Felipe de Melo Gomes (2024)
This dissertation is the result of an ethnographic research developed with the Maroon Community of Atalho, Monte Carmelo – MG. At the first meetings I had with the community leaders, the association's members did not declare themselves as maroons, but throughout the research process, they decided to adopt the use of this identity as a political tool. The maroon identity application process, that was along the State, and the kinship relations, that are shaped as a community, will be described simultaneously. The timeline of this whole discussion will be based on the “native” way of establishing what is “inside” or “outside” of the community. The three chapters that compose this dissertation are an effort to trace a sketch/ blueprint about three native theories that intersect with each other, they concern the notions of “Politics”, “Knowledge” and “Race”. In the first chapter I attempted to describe the kinship relations and their political operation, which brings many epistemological elements to the discussion. In the second chapter, their relationship description with others-than-human beings brings to the heart of the matter a knowledge theory which I have named "epistemology of sensitivity", that in its practical dimension demonstrates the cosmopolitical compositions of my interlocutors. Finally, by bringing a native notion of “Race", I sought to articulate the discussions regarding religion, kinship, politics, others-than-human beings and knowledge which were constantly perceived in my relationships with the members of the community.